Architecture of Migration The Dadaab Refugee Camps and Humanitarian Settlement (Theory in Forms, 2024)
Focusing on the Dadaab refugee camps established in 1991 on the Kenya-Somalia border, Anooradha Iyer Siddiqi shows how a refugee camp's aesthetic and material landscapes-even if born out of emergency-reveal histories, futures, politics, and rhetorics.